Pengaruh Persepsi dan Preferensi Mahasiswa Terhadap Perilaku Investasi di Galeri Investasi Syariah - Mira Oktarina; Novia Nengsih (MABIS: Jurnal Manajemen Bisnis Syariah, 2023)
This research aims to determine the influence of perceptions and preferences on investment behavior at the Sharia Investment Gallery. This research is field research using a quantitative approach. Sampling used random sampling techniques or random samples with a population of 132 Sharia Business Management Study Program students, and to determine the sample using the Slovin formula to obtain 57 samples. The results of the research state that perception (X1) has a significant influence on Investment Behavior (Y) in the Sharia Investment Gallery. Preference (X2) has a significant influence on Investment Behavior (Y) in the Sharia Investment Gallery. Perception (X1) and Preference (X2) have an influence simultaneously on Investment Behavior (Y) in the Sharia Investment Gallery